Reasons for underrepresentation of female leaders and figureheads in Finland according to male sport executives - Ruotsalainen, Susanna (2019)
Scarcity of female leaders in sport organizations has been recognized as a worldwide dilemma. This research focuses on its prevalence specifically in Finland. Although women in Finland in general are quite fortunate to be able to enjoy a relatively high level of equality in most aspects of life, the blatant underrepresentation of female leaders and figureheads particularly in sports is somewhat mysterious and is worth investigating further. In the last two decades, more women have been appointed to sport leadership positions in Finland, but the highest and most influential positions are still occupied mainly by male.